Analisis Faktor-Faktor Biaya Mutu Pada Proses Produksi Nira Di Stasiun Penggilingan Tebu (Stations Mill Cane) Di PT Gunung Madu Plantations - Eri Wijaksana; Melani Anggraini; Sulastri Sulastri (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2016)
Abstract. Cane is one of the agricultural commodities that have a good prospect to be developed as anindustrial raw material, in particular white sugar. Along with industrial development and populationincreasing, the need for sugar is increasing therefore the PT. Gunung Madu Plantations continues todevelop its existence in the increase of fresh sugar cane plantations (PTS) and the use of cost onsugar mill (mill cane).The purpose of this study was to analyze the use of quality costs incurred bythe company to the extent of damage Nira Cane, to analyze how much influence the cost of the qualityof the product quality improvement Nira Sugarcane at PT. Gunung Madu Plantations. the methodsthat used in this study is a qualitative analysis and multiple regression analysis. Based on the resultsof the regression analysis between the cost of the quality of the degree of damage Nira Sugarcaneproduction, which suggests that factors such as the quality costs (prevention costs, appraisal costs,internal failure costs and external) significant influence, because the p value (significance F value) offourth the cost of a quality below 0.05. Cost control quality made by the company, showing that thedevelopment cost of quality from year to year has increased from 2010 - 2014. With the increased,cost of quality, resulting in damage levels of Nira Sugarcane production can be decreased, especiallythe cost of prevention and appraisal costs.